(untitled) - Muschla, Judith A. (San Francisco, 2006)
Hands-on math projects with real-life applications, second edition offers an exciting collection of 60 hans-on projects to help students in grades 6-12 apply math concepts and skill to solving everyday, real-life problems! The book is filled with classroom-testted projects that emphasize : cooperative learning, group sharing, verbalizing concepts and idea.
Keywords: Mathematics,Activity programs in education; study and teaching.,activity programs